Heart rate turbulence in patients after primary percutaneous coronary intervention and fibrinolytic treatment for acute myocardial infarction (Medical Journal of Indonesia, 2007)
Heart rate turbulence (HRT) as novel predictor of sudden cardiac death were superior to all other presently available indicators. HRT significantly was improves after successful reperfusion reflecting rapid restoration of baroreceptor response. We investigated turbulence onset (TO) and turbulence slope (TS) values among patients with acute ST-elevation myocardial infarction (STEMI) underwent revascularization by means of primary PCI or fibrinolytic. We hypothesized that the values of TO and TS were different in two kinds of revascularization treatment. The subjects underwent 24 hours ECG recording after revascularization therapy. TO was quantified by the relative change of the first two sinus RR intervals following a ventricular premature beat (VPB) and the last two sinus RR intervals before the VPB. TS was quantified by the maximum positive slope of a regression line assessed over any sequence of five subsequent sinus rhythm RR intervals within the first two sinus rhythm intervals after a VPB. Thirteen patients (mean of age 56± 9 years old) who underwent revascularization treatment of acute STEMI were eligible as subject of this study.Ten patients underwent fibrinolytic therapy and three patients underwent primary PCI. TO value was significantly different between PCI group and fibrinolytic group (-3.3± 1.7 % vs -0.2± 0.9 % ; P=0.03). The Primary PCI group has better outcome on turbulence slope value (TS) than fibrinolytic group but not significance (7.7± 4.4 msec/RR interval vs 3.4± 2.6 msec/RR interval; P = 0.056). In conclusion, TO was better in acute STEMI patient undergone PCI compare to that undergone fibrinolytic therapy. (Med J Indones 2007; 16:19-24) Keywords: heart rate turbulence, revascularization, myocardial infarction